Structural Model of Children’s Behavioral Problems Based on Mothers’ Adverse Childhood Experiences with the Mediating Role of Maternal Mentalization - Kejani, Mina; Ansari Shahidi, Mojtaba; Faramarzi , Salar; Khanzadeh, Mostafa (Psychology of Woman Journal, 2025)
Objective: This study aimed to investigate the structural model of children’s behavioral problems based on mothers’ adverse childhood experiences (ACEs), with maternal mentalization as a mediating factor.Methods and Materials: A correlational design using structural equation modeling (SEM) was employed. The sample consisted of 323 mothers with children aged 6 to 12 years in Isfahan, selected through convenience sampling during 2023–2024. Data were collected using the World Health Organization’s Adverse Childhood Experiences International Questionnaire (ACE-IQ), the Achenbach Child Behavior Checklist (CBCL) parent version, and the Persian version of the Reflective Functioning Questionnaire (Mentalization Questionnaire). Data analysis was conducted using SPSS-24 and AMOS-24, applying confirmatory factor analysis, maximum likelihood estimation, and bootstrapping with 2,000 resamples to test direct and indirect pathways.Findings: The results revealed that maternal ACEs were positively and significantly associated with children’s internalizing and externalizing behavioral problems. Maternal ACEs were also negatively and significantly related to maternal mentalization. In turn, maternal mentalization showed a significant negative relationship with children’s behavioral problems. Structural modeling confirmed that maternal mentalization partially mediated the relationship between maternal ACEs and children’s behavioral outcomes. Bootstrapping results demonstrated that the indirect effects of maternal ACEs on both internalizing and externalizing problems through maternal mentalization were statistically significant. Model fit indices indicated acceptable to excellent fit across all parameters, supporting the robustness of the structural model.Conclusion: The findings highlight the intergenerational transmission of adversity, demonstrating that mothers’ adverse childhood experiences contribute to children’s behavioral problems both directly and indirectly through diminished maternal mentalization. Strengthening maternal reflective functioning may serve as a critical intervention target to reduce the negative impact of maternal trauma histories on child behavioral outcomes. These results emphasize the importance of trauma-informed, family-centered interventions to disrupt cycles of adversity and promote healthier socioemotional development in children.